Kajian Semiotika Tari Piring Dua Belas di Tanggamus - Juwita, Dwi Tiya (Aksara: Jurnal Bahasa dan Sastra, 2024)
This research aims to examine the Piring Dua Belas dance from a semiotic perspective. This research uses qualitative methods with descriptive analysis. This research uses the Semiotics theory by Charles Sanders Peirce. The results of this research showed in this type of movement, ngakhakelap means that if you have a need, you should meet someone directly without going through an intermediary. It is feared that other people who intervene can exaggerate or reduce everything that should be conveyed. The various movements of sebatang masuk and sebatang keluar have the meaning of advice that life must follow its course like the flow of a river. The variety of ngahilok movements means that Lampung people when walking in front of penyimbang should walk normally and do not need to walk down or squat. The various movements of the laga puyu mean that all problems that occur should be resolved immediately by the person concerned. The variety of nokokh movements means that in living life you have to be skilled. The property used means that in everything there must be two, there is winning and there is losing, there is sadness and happiness. The music that accompanies the dance means that the community, traditional leaders and artists of the Piring Dua Belas dance have tried to maintain the existence of this dance by trying to adapt it to current life. The overall meaning implied in the Piring Dua Belas dance is advice given to people in living their lives. Keywords: Piring Dua Belas Dance, Semiotic